2004 Annual Conference Proceedings
DOI: 10.18260/1-2--12832
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Cooperative Learning Events For Engineering Classes

Abstract: Faculty value high student engagement that leads to high learning outcomes. While high student engagement is frequently difficult to achieve, numerous studies have shown that cooperative learning events produce greater student engagement in a wide variety of disciplines. However, many students have had negative experiences with "group work" and are hesitant to participate. In addition, it can be unclear when creating a cooperative educational event for engineering classes whether it will work as planned. Our q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This finding is in line with that of Zemke, Elger & Beller (2004) who found that students overwhelmingly indicated that the use of effective events enabled them to more easily master different material in cooperative learning group. He further stated that those students who worked in smaller groups in cooperative learning strategy were better motivated to learn physics; this might be as a result of better accessibility to the teacher during teaching and learning process than in the Traditional method class.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…This finding is in line with that of Zemke, Elger & Beller (2004) who found that students overwhelmingly indicated that the use of effective events enabled them to more easily master different material in cooperative learning group. He further stated that those students who worked in smaller groups in cooperative learning strategy were better motivated to learn physics; this might be as a result of better accessibility to the teacher during teaching and learning process than in the Traditional method class.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, Zemke, Elger and Beller (2004) found that students overwhelmingly indicated that the use of effective events in Cooperative learning groups enabled them to more easily master difficult materials. This was a clear indication that the way the subject was taught needed to be looked into.…”
Section: Statement Of the Problemmentioning
confidence: 99%